2014
DOI: 10.1093/ageing/afu144
|View full text |Cite
|
Sign up to set email alerts
|

Functional status and co-morbidities are associated with in-hospital mortality among older patients with acute decompensated heart failure: a multicentre prospective cohort study

Abstract: Co-morbidities and functional impairments are associated with a worse short-term prognosis in patients aged ≥75 years admitted for ADHF. Assessing these parameters at admission may improve patient management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
2
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 30 publications
0
29
2
3
Order By: Relevance
“…Renal function is one of the most powerful determinants of prognosis in AHF and is part of most risk scores for ADHF . Creatinine clearance has been proven to be an independent prognostic factor for in‐hospital mortality of older patients with ADHF . In patients with impaired renal function NT‐proBNP concentrations are raised and correlated to renal function; however, in our study both NT‐proBNP and eGFR entered into the final model and were independently correlated to prognosis.…”
Section: Discussionmentioning
confidence: 53%
“…Renal function is one of the most powerful determinants of prognosis in AHF and is part of most risk scores for ADHF . Creatinine clearance has been proven to be an independent prognostic factor for in‐hospital mortality of older patients with ADHF . In patients with impaired renal function NT‐proBNP concentrations are raised and correlated to renal function; however, in our study both NT‐proBNP and eGFR entered into the final model and were independently correlated to prognosis.…”
Section: Discussionmentioning
confidence: 53%
“…The pooled HRs from 2 studies revealed a significant increase in LOS in the cohort with elevated cTn (OR: 1.05, 95% CI: 1.01‐1.10, P = 0.06, I 2 = 59.5.0%, n = 949). Six studies assessed in‐hospital mortality, and the meta‐analysis showed a significant increase in the risk of death with no significant heterogeneity (OR: 2.57, 95% CI: 2.27‐2.91, P = 0.744, I 2 = 0.0%, n = 69,524). Similarly, 4 clinical studies found detectable or elevated cTn as a predictor of worsened composite clinical outcomes of death and major cardiovascular events (OR: 1.33, 95% CI: 1.03‐1.71, P = 0.473, I 2 = 0.0%, n = 1,313).…”
Section: Resultsmentioning
confidence: 98%
“…[46, 47] We have demonstrated previously that functional status mediates the relationship between poor quality of life and cardiac event-free survival in heart failure. [46] These two prognostic indicators of poor outcomes are easily assessed in the clinical setting and provide important targets for intervention.…”
Section: Discussionmentioning
confidence: 99%